Photocatalytic degradation kinetics of unsymmetrical dimethylhydrazine in aqueous solution by Fe3+ doped Bi2O3. (February 2019) - Qi, J; Zhao, B; Wang, Y; Wu, Y; Xu, Z L; Hou, Z W; Yan, J J
Abstract: The Fe 3+ doped Bi2 O3 photocatalyst was prepared by sol-gel method. The photocatalytic degradation experiment was carried out using unsymmetrical dimethylhydrazine (UDMH) simulated wastewater as the target pollutant. The results showed that Fe 3+ doping significantly improved the degradation efficiency of UDMH with an optimum doping concentration of 2.0%. The reaction kinetics study indicated that the reaction was heterogeneously catalyzed and the kinetic fitting results were consistent with pseudo first-order reaction kinetics model. According to the results of linear fitting, the kinetic reaction rate constant of Fe 3+ doped Bi2 O3 (2.0%) was the largest, about 1.9 times as much as that of undoped Bi2 O3 . Finally, a possible mechanism was proposed to explain the enhanced photocatalytic activity.